2010
DOI: 10.1016/j.brainres.2009.12.089
|View full text |Cite
|
Sign up to set email alerts
|

Microglial response to murine leukemia virus-induced encephalopathy is a good indicator of neuronal perturbations

Abstract: The neuronal pathology caused by neonatal infection of rats with the PVC-211 murine leukemia virus (PVC-211 MuLV) and its underlying mechanisms are not well defined even though a loss of neurons and spongiform neurodegeneration has been reported to accompany the disease. Here we sought to identify sites of neurodegeneration using microglial reactivity as an indirect marker and to characterize microglial activation during disease progression. Using a panel of microglial antibodies including Iba1, OX-42, ED1, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The spatial distribution of the virus within the CNS (e.g. parenchyma or blood vessels) is not well defined [84]. In this study, we did not address modes of MoMuLV replication in brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spatial distribution of the virus within the CNS (e.g. parenchyma or blood vessels) is not well defined [84]. In this study, we did not address modes of MoMuLV replication in brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Mice infected with MoMuLV alone did not show any clinical signs of disease or neuropatholgical alterations. Here, it is important to note that the administration of virus to young mice and not to mid-gestation or newborn mice, inhibits disease induction (both the common T-cell lymphoma/leukemia and a very rare spongiform encephalopathy induced by mutant forms of MoMuLV) by reducing virus spread at a critical developing window in both the thymus and CNS [4,55,61,84]. Furthermore, the development of paresis in MoMuLV ?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situations where there is sudden entry of iron into the CNS parenchyma, for example during intracerebral hemorrhages, it is of critical importance that the iron be sequestered rapidly and effectively, and this is a critical function of microglial first responders. Experimental studies in animals have shown that when microhemorrhages occur or when there is CNS trauma, microglia not only become positive for ferritin they also become dystrophic [ 143 , 144 ]. The strong correlation between ferritin positivity and dystrophy, reflected in findings from both human brains as well as from experimental studies, strongly suggest that sequestration of iron is a hazardous activity that can cause damage to microglial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In general, microglial induction is thought to be protective, with the goal of eliminating the encountered pathological species. However, this activation can also have unintended consequences, leading to neurotoxicity [ 12 ]. For this reason, mechanisms exist to deactivate the microglial response.…”
Section: Introductionmentioning
confidence: 99%